Participação da ativação da via IL-33/ST2 na indução da resposta imunológica, na diferenciação de macrófagos e na fibrose induzida pela infecção por Schistosoma mansoni - Laura Liana Maggi Fernandes (2021)
The release of antigens secreted by Schistosoma mansoni eggs that are trapped in tissues, especially the liver, induce a type 2 (Th2) granulomatous inflammatory response, which is crucial for the evolution of schistosomiasis morbidity. IL-33 and its ST2 receptor, are expressed by several innate immune cells, such as macrophages, eosinophils, type II innate lymphocytes that stimulate the early production of cytokines, such as IL-13 and IL-5, and participate in the immune response responsible for granuloma formation and the evolution of the hepatic fibrosis process. Therefore, in this work we idealized the evaluation of the participation of the IL-33/ST2 pathway in the formation and modulation of hepatic granulomas, in the development of fibrosis and in the activation and differentiation of macrophages. Thus, we comparatively evaluated the immune response and granuloma formation in BALB/c (WT) and BALB/c genetically deficient mice without IL-33 receptor (ST2-/-) experimentally infected with S. mansoni. These animals were followed for up to 14 weeks to assess mortality. Then, the parasite load, hepatic immune response, formation of hepatic granulomas, as well as the fibrosis process and the participation of different types of macrophages involved in this context were evaluated. Our data showed that the parasite load was similar in WT and ST2-/- mice, but the ST2-/- infected animals showed an increased mortality rate. The absence of IL-33 activation did not alter the induction of the Th2 response and led to a predominance of Th17 in liver tissue. Hepatic granulomas from deficient animals presented hydroxyproline content similar to WT, however, these are larger and with intense cellular infiltrate, rich in eosinophils and neutrophils. The granuloma of deficient animals also presented a disorganized extracellular matrix, justified by the reduction in the activation of HSC and its transdifferentiation into myofibroblasts, despite the increased expression of TGF-β. This impacted the reduced expression of Col III and Col VI in ST2-/- mice, a fact that was accompanied by a reduction in the formation of reticular fibers in the extracellular matrix of the granuloma. In vitro macrophage profile evaluation indicated that monocytes retrieved from the bone marrow of ST2-/- mice and stimulated to differentiate into M1 and M2 produce lower levels of arginase and higher levels of nitrite compared to differentiated WT cells. In experimental schistosomiasis it was also detected variation in the activation of M2 macrophages in the liver of ST2-/- mice compared to WT, with increased expression of ARG-1 and arginase activity and reduction of MgL2 and Chi3l3 in the acute phase of the infection, suggesting greater activation of M2a. On the other hand, in chronic schistosomiasis these animals had a significant increase in NOS-2 expression in liver tissue, indicating an increase in M1 macrophages. The data indicate that activation of the IL-33/ST2 pathway is not essential for the induction of the Th2 response, but it is necessary for the modulation of the Th17 response, adequate macrophage differentiation, for differentiation of HSC into myofibroblasts and production of different collagens, allowing the formation of reticular fibers and the formation of hepatic granulomas capable of reducing tissue damage and controlling host mortality during schistosomiasis.